1983
DOI: 10.1016/0014-5793(83)80254-3
|View full text |Cite
|
Sign up to set email alerts
|

Islet‐activating protein prevents nicotinic acid‐induced GTPase stimulation and GTP but not GTPγS‐induced adenylate cyclase inhibition in rat adipocytes

Abstract: The influence of islet-activating protein (IAP), a Bordetella pertussis toxin, was studied on adenylate cyclase and GTPase activities in rat adipocyte membranes. Pretreatment of rats or intact rat adipocytes with IAP did not affect adenylate cyclase inhibition by the stable GTP analog, GTP$$ whereas inhibition by GTP was abolished. Concomitantly, activation of the adipocyte enzyme by sodium and its inhibition by nicotinic acid were prevented. Furthermore, IAP treatment of adipocyte membranes prevented nicotini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 17 publications
3
20
0
Order By: Relevance
“…In agreement with a previous report (Aktories et al, 1983), we have found that G protein activation by nicotinic acid in adipocyte membranes is sensitive to pertussis toxin. However, [ 3 H]nicotinic acid to spleen membranes was inhibited by the toxin only to a minor extent.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In agreement with a previous report (Aktories et al, 1983), we have found that G protein activation by nicotinic acid in adipocyte membranes is sensitive to pertussis toxin. However, [ 3 H]nicotinic acid to spleen membranes was inhibited by the toxin only to a minor extent.…”
Section: Discussionsupporting
confidence: 94%
“…It has been reported previously that GTPase activation and adenylyl cyclase inhibition by nicotinic acid in adipocyte membranes are pertussis toxin-sensitive (Aktories et al, 1983). In agreement with these findings, we found that pertussis toxin pretreatment of rat adipocyte membranes reduced stimulation of […”
Section: Nicotinic Acid Stimulates [supporting
confidence: 92%
See 2 more Smart Citations
“…KCI, which extracts peripheral proteins, could conceivably further decrease the number of membranebound N proteins. Due to possible changes in the stoichiometric ratio between N and receptor molecules, similar hormonal responses may require activation of more receptors and, ( I mglml) were preincubated in the absence or presence of 1 pg/ml of trypsin (Sigma) at 33 ~ C. The incubation medium contained 25 mM Tris/HCI, pH 7.6 and 0.05 2, bovine serum albumin. After 5 min, soybean trypsin inhibitor (Sigma) was added to both the trypsin-treated and control membranes at a final concentration of 10pg/ml and 4O-pl therefore, higher hormone concentrations in isolated membranes compared to intact cells.…”
Section: Discussionmentioning
confidence: 99%